Respostas

2013-07-31T23:09:51-03:00
Resolvendo a equação, temos:

x^{2}-9x+8=0

\Delta=b^{2}-4\cdot a\cdot c
\Delta=(-9)^{2}-4\cdot1\cdot8
\Delta=81-32
\Delta=49

x=\dfrac{-b\pm\sqrt{\Delta}}{2a}

x=\dfrac{9\pm\sqrt{49}}{2\cdot1}

x=\dfrac{9\pm7}{2}

\Longrightarrow\;x_{1}=\dfrac{9+7}{2}=\dfrac{16}{2}=8

\Longrightarrow\;x_{2}=\dfrac{9-7}{2}=\dfrac{2}{2}=1

S=\{1,\;8\}
1 3 1
2013-07-31T23:10:11-03:00
-x^2-9x+8=0
a=1
b=-9
c=8

x= -b + sqrt{delta}/2*a

x= -b - sqrt{delta}/2*a

delta = b²-4*a*c
delta = (-9)²-4*1*8
delta = 81-32
delta = 49


x= -(-9) + sqrt{49}/2*1
x= 9 + 7/2
x= 16/2
x=8


x= -(-9) - sqrt{49}/2*1
x= 9 - 7/2
x= 2/2
x=1

sqrt{delta} significa raíz de delta